Correlation between Gut Microbiota and Lung Cancer. - Jun TENG; Yanfen ZHAO; Yunning JIANG; Qi WANG; Yongsheng ZHANG (Chinese Journal of Lung Cancer, 2020)
Gene-environment interactions underlie cancer susceptibility and progression. The human body is exposed to and affected by the microenvironment seiscasts of various microorganisms and their metabolites, such as the microenvironment of gut microbiota. The relative abundance of some intestinal microbes in lung cancer patients was significantly different from that in the control group. These studies suggest that gut microbiota may be associated with lung cancer through some ways. At the same time, gut microbiota is relatively manageable environmental variables compared to the external environment we are exposed to, as they are highly quantifiable and relatively stable in the individual. Just as some measures of diagnosis, intervention and treatment of lung cancer targeting gut microbiota have achieved some results in clinical practice. In this review, we mainly discuss the role of gut microbiota and its metabolites in the progression and treatment of lung cancer through certain ways, such as regulation of metabolism, inflammation, and immune response. Finally, based on current research progress, it is inferred that research on gut microbiota may be an effective approach to the precise and personalized medical treatment of lung cancer.